2023
DOI: 10.15391/prrht.2023-8(2).01
|View full text |Cite
|
Sign up to set email alerts
|

Changes in physical activity indicators of Ukrainian students in the conditions of distance education

Abstract: Purpose: purpose of the work is to determine the changes in physical activity indicators of Ukrainian students in the conditions of distance education caused by the quarantine restrictions and the conditions of the legal regime of martial law. Material & Methods: the study, which lasted from 2020 to 2023, involved 1528 higher education students from different regions of Ukraine. The International Physical Activity Questionnaire (IPAQ) was used to assess physical activity. The results were subjected to sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 18 publications
0
6
1
1
Order By: Relevance
“…The fact that gender did not turn out to be a significant factor affecting the stress-related condition of the category of youth under research was an interesting and unexpected result for us. This contradicts not only the data given in scientific sources (Pavlova et al, 2022;Rogowska &Pavlova, 2023;Levin et al, 2022;Petrachkov et al, 2023) but also our previous research where we found that female students reported symptoms of stress-related conditions more often than male students (Andrieieva et al, 2023;Byshevets et al, 2023). It is important to note that in previous research, either a separate comparative analysis of indicators of stress-related conditions depending on gender was carried out, or there was used the data obtained by respondents' reporting on the regularity of their activity (No/Rather not/Rather yes/Yes), but the results of measuring the level of their PA according to the IPAQ were not taken into account.…”
Section: Discussioncontrasting
confidence: 98%
See 3 more Smart Citations
“…The fact that gender did not turn out to be a significant factor affecting the stress-related condition of the category of youth under research was an interesting and unexpected result for us. This contradicts not only the data given in scientific sources (Pavlova et al, 2022;Rogowska &Pavlova, 2023;Levin et al, 2022;Petrachkov et al, 2023) but also our previous research where we found that female students reported symptoms of stress-related conditions more often than male students (Andrieieva et al, 2023;Byshevets et al, 2023). It is important to note that in previous research, either a separate comparative analysis of indicators of stress-related conditions depending on gender was carried out, or there was used the data obtained by respondents' reporting on the regularity of their activity (No/Rather not/Rather yes/Yes), but the results of measuring the level of their PA according to the IPAQ were not taken into account.…”
Section: Discussioncontrasting
confidence: 98%
“…As shown by the results of previous research (Andrieieva et al, 2023;Byshevets et al, 2023), the level of stress-related conditions of students is determined by numerous factors, including controlled and uncontrolled ones. Some of them increase the risk of stress-related conditions of students, while others allow them to counteract the negative consequences of stress factors.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Among the most effective measures for overcoming stress among student youth, scientists single out participation in health and recreational activities, meditation, breathing practices, and physical exercises (Andrieieva et al, 2023;Hakman et al, 2020). Among the scientific community, there is widespread opinion about the benefits of using mental fitness tools, such as yoga and Pilates (Shelikhova et al, 2021), to reduce the effects of adverse stressors in university students (Kashuba et al, 2020).…”
Section: Introductionmentioning
confidence: 99%